Captive Green Iguana Carries Diarrheagenic Escherichia coli Pathotypes - Bautista-Trujillo, Gerardo Uriel; Gutiérrez-Miceli, Federico Antonio; Mandujano-García, Leonel; Oliva-Llaven, María Angela; Ibarra-Martínez, Carlos; Mendoza-Nazar, Paula; Ruiz-Sesma, Benigno; Tejeda-Cruz, Carlos; Pérez-Vázquez, Liset Candelaria; Pérez-Batrez, Jesús Eduardo; Vidal, Jorge E.; Gutiérrez-Jiménez, Javier (Frontiers in Veterinary Science, 2020)
The green iguana appears to be a carrier for bacteria causing gastrointestinal infections in humans. The presence of diarrheagenic E. coli (DEC) pathotypes , however, has not been studied in this reptile. The aim of the current work was to investigate the prevalence of DEC in the intestines of 240 captive green iguanas, their phylogenetic groups, and the antibiotic susceptibility profile. E. coli strains were isolated from 41.7% (N=100/240) of the intestinal content of green iguanas. DEC strains was identified in 25.9% of the screened population and were detected in the majority (62%, p=0.009] of those reptiles carrying E. coli strains. Among DEC strains, STEC strains carrying the stx1 gene were the most prevalent pathotype isolated (38.7%), followed by EAEC and ETEC (27.4% each). Genetic markers of DEC strains belonging to the EHEC pathotype were not detected. More than a half of DEC strains were classified into the Clade I-II phylogroup (64.5%), followed by the phylogroup A (14.5%). The antibiotic susceptibility method demonstrated that a high proportion of DEC strains were resistance, or non-susceptible, to carbenicillin, amikacin, and ampicillin. We conclude that the green iguana kept in captivity is a carrier of DEC strains bearing resistance to first-line antibiotics, including penicillins. Given the increase presence of the green iguana in Latin American households, these reptiles represent a potential source of transmission to susceptible humans and therefore a potential source of gastrointestinal disease.